Teaching geographies of the far-right in Germany – conceptualising hate and fear as didactic challenges - Kübler, Felicitas; Schopper, Tobias (2023)
Abstract: The focus of this paper is the affective dimension of far-right discourses which we consider challenges for teaching. The rise of the far-right in many parts of the world has led to a growing body of work in the social sciences. However, as the topic has become the subject of academic scrutiny its controversial nature also demands a debate on teaching strategies and principles. Drawing on two courses on the political geography of the far-right taught at two German universities, we propose paying special attention to the affective potentials of far-right discourses and taking a normative anti-fascist approach to facilitate critical thinking, solidarity, and empathy in the classroom. Additionally, we also urge educators to pay close attention to emotions students might experience when analysing and discussing the far-right. This paper situates the case studies within the context of far-right mobilisations in Germany and describes the challenges of developing the syllabus and the teaching strategies. It concludes with data from a survey amongst students who attended the courses on the perception and emotional reaction towards the far-right showing that students are affected and potentially frustrated given the current success of the far-right but also see the need for counter action